Islamic Religious Education For Autism at SLB Autisma Dian Amanah Sleman Yogyakarta - Husna, Difa'ul; Nur Cholifah, Fitri (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
Autism was first introduced by Leo Kramer, a psychiatrist from Harvard, in 1943. People with autism, among others, have symptoms of difficulty interacting, communicating strangely, not caring about the surrounding environment, having their own world, and having difficulty accepting change. Therefore, they need accommodations in the learning process. Researchers use descriptive and qualitative methods to describe the data obtained through the use of interview techniques, documentation, and observation. Data analysis goes through stages in the form of data reduction, presentation, and drawing conclusions. Checking the validity of the data is carried out using triangulation techniques. Based on research, PAI learning in children with autism at SLB Autisma Dian Amanah Yogyakarta is carried out by identifying and determining the specifications and qualifications for changes in student behavior, determining the learning approach system, establishing learning procedures, methods, and techniques, as well as criteria for learning success.